2018
DOI: 10.1364/boe.9.002810
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic 3D-printed neurovascular phantoms for near-infrared fluorescence imaging

Abstract: Emerging three-dimensional (3D) printing technology enables the fabrication of optically realistic and morphologically complex tissue-simulating phantoms for the development and evaluation of novel optical imaging products. In this study, we assess the potential to print image-defined neurovascular phantoms with patent channels for contrast-enhanced near-infrared fluorescence (NIRF) imaging. An anatomical map defined from clinical magnetic resonance imaging (MRI) was segmented and processed into files suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The introduction of multi-material 3D printing may ease the development of anatomically relevant phantoms, since the phantoms can be built up layer by layer allowing complex structures to be embedded. Inspiration may be taken from phantoms designed for x-ray imaging [40,41] and fluorescent brain imaging [42]. However, due to limited available 3D printing materials, it is not possible yet to print PA phantoms with both optical and acoustic properties matching the body's soft tissues.…”
Section: Photoacoustic Phantomsmentioning
confidence: 99%
“…The introduction of multi-material 3D printing may ease the development of anatomically relevant phantoms, since the phantoms can be built up layer by layer allowing complex structures to be embedded. Inspiration may be taken from phantoms designed for x-ray imaging [40,41] and fluorescent brain imaging [42]. However, due to limited available 3D printing materials, it is not possible yet to print PA phantoms with both optical and acoustic properties matching the body's soft tissues.…”
Section: Photoacoustic Phantomsmentioning
confidence: 99%
“…Identifying a suitable channel size involved printing a sample with a range of different channel diameters and using micro-CT imaging to identify the smallest channels that were consistently patent. We previously found that to ensure patency, diameters of approximately 0.8-1 mm were required in biomimetic 3D curved channels [32,33]. This limitation highlights the need for printer quality testing of samples over a range of channel diameters.…”
Section: Evaluation Of Phantom Morphology and Optical Propertiesmentioning
confidence: 99%
“…While we are not aware of any subsequent studies implementing this type of high-density channel-array approach for NIRS, it may now be possible to generate similar phantoms with less effort and greater flexibility using 3D printing technology. Our lab has pioneered the fabrication of 3D-printed biophotonic phantoms [31], developing models with both idealized and biomimetic vascular geometries for evaluation of hyperspectral and fluorescence imaging systems [31][32][33]. Other groups have also shown success in developing 3D-printed phantoms for different biophotonic applications [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Phantoms have become increasingly capable of modeling not only the structural characteristics of human anatomy but also the functional attributes. Many phantoms are trending toward having functional attributes and various studies have begun to develop functional phantoms [34][35][36][37][38] with vascular anatomy.…”
Section: Future Of Phantom Designmentioning
confidence: 99%